2002
DOI: 10.1002/smi.915
|View full text |Cite
|
Sign up to set email alerts
|

Responding to daily event questionnaires: the influence of the order of hassle and uplift scales

Abstract: Two studies demonstrated differences in hassle and uplift ratings of daily events as a function of questionnaire order and format. In the first study, 123 undergraduates rated 143 events as both sources of hassles and sources of uplifts. The order of completion of hassle and uplift ratings had a substantial impact on uplift ratings, but only a minor impact on hassle ratings. Events were rated less uplifting when these ratings followed rather than preceded hassle ratings. The second study replicated this asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Because the effort of re-memorising a negative event has a stronger impact on the mood of the responder, it was necessary to avoid the responder's response contaminating the next item of opposite valence (Maybery et al, 2002). We thus decided to divide our 58 categories of events into two separate lists according to the majority valence of the verbatim enclosed.…”
Section: Occurrence and Intensity Of Eventsmentioning
confidence: 99%
“…Because the effort of re-memorising a negative event has a stronger impact on the mood of the responder, it was necessary to avoid the responder's response contaminating the next item of opposite valence (Maybery et al, 2002). We thus decided to divide our 58 categories of events into two separate lists according to the majority valence of the verbatim enclosed.…”
Section: Occurrence and Intensity Of Eventsmentioning
confidence: 99%
“…Not only can a sad and depressed mood trigger the recall of past similar events, recalling sad and depressing events can affect current mood [55,56]. An attempt at controlling this effect by the design of instrument scales has been described by Maybery et al [56]. They reported that, by altering the format of questionnaires, different outcomes may be observed.…”
Section: Future Recommendationsmentioning
confidence: 99%
“…Stress and coping instruments typically have a quantitative focus and some have been revised in response to criticism of their weak psychometric properties, unstable factor structures and lack of cross‐validation (De Ridder 1997, Maybery & Graham 2001, Maybery et al. 2002).…”
Section: Introductionmentioning
confidence: 99%